A Constructivist Approach in Nonformal Education: Case Study of Developing Pancasila Leadership Character - Sarwo Edy; Dasim Budimansyah; Encep Syarief Nurdin; Mupid Hidayat (Journal of Nonformal Education, 2025)
Background: Nonformal education plays a strategic role in character formation, particularly in shaping leadership qualities rooted in national values. This study explores the implementation of a constructivist approach in nonformal education settings to develop leadership character based on Pancasila principles.   Objectives: The research aims to analyze how constructivist-based learning strategies can be applied in nonformal education as an effective framework for cultivating Pancasila leadership values among learners.   Method: This study employed a qualitative design through literature review, observation, and interviews with learners and facilitators in nonformal education programs. Data were analyzed descriptively to evaluate the relevance, effectiveness, and contextual impact of constructivist practices.   Findings: The application of experiential learning, dialogic discussions, collaborative projects, and contextual case studies enhanced learners’ comprehension of Pancasila principles and fostered leadership values such as integrity, responsibility, and social empathy. Integration of digital media and adaptation to community contexts further strengthened the relevance of the learning process.   Conclusion: A constructivist approach in nonformal education is effective not only in reinforcing knowledge of Pancasila but also in nurturing leadership characters aligned with inclusivity, democracy, and social justice. This model has the potential to prepare future leaders who are responsive to societal challenges while upholding Indonesia’s core values.   Novelty: The study highlights a practical constructivist framework in nonformal education that explicitly integrates Pancasila leadership values with modern pedagogical strategies, offering a contextual model for leadership character education in Indonesia.